LOCAL WISDOM OF NIAS TRADITION ORAHU - Boiolifu Bu’ulolo (Universitas Islam Sumatera Utara (UISU), 2020)
Orahu is a tradition of deliberation which is well known in the life system of the people of South Nias, especially in the areas of Maniamölö, Onolalu, To'ene and Mazinö. Orahu is carried out in every important activity in the community, for example discussing problems related to the village, death events, weddings, Fa'ulu and Mambu Ana'a parties (ceremony to increase social status or traditional parties) and others. Orahu to a large extent is called Orahua Mbanua, and is usually performed at Ewali Sawolo or Ewali Orahua (the courtyard in front of the house of the most influential nobleman or Balö Ji'ulu). The Orahua Mbanua was followed by the Si'ulu (nobles), Si'ila (traditional leaders) and Ono Mbanua (the whole community). This research was aimed at describing as well as revealing the local wisdoms of Orahu. This research applied qualitative descriptive method. The data in this study were collected using interview techniques and literature study. The research results shows that Orahu tradition emphasizes on the solidarity and wise decision taking which become a very important aspect in the life system of Nias people. It was in this open forum that all village problems were discussed, and decided how to handle them. In ancient times, Orahu was also used as a trial and for determining punishment for violators of village customs. Orahu is usually done at the bale (village meeting hall), but to a lesser extent, it can also be carried out at home.